Prediktor Quiet Quitting Pada Karyawan Era PascaPandemi: Systematic Literature Review dan Bibiometric Analysis - Pasha, Belvania Maulidhya; Soetjipto, Budi Eko (JURNAL MANAJEMEN MOTIVASI, 2026)
Quiet Quitting has gained attention in the post-pandemic era, reflecting employees' psychological withdrawal despite fulfilling formal duties. This study conducts a Systematic Literature Review and bibliometric analysis of 46 Scopus-indexed articles (2015–2025) to explore its predictors. Findings show a surge in publications since 2023, led by scholars such as Galanis, Aglaia, and Ioannis, with India, Greece, and Turkey as top contributors. Key drivers include individual psychology, work environment, and socio-cultural factors, aligned with Psychological Contract Theory. The study highlights the importance of empathetic leadership, flexible policies, and fair rewards to prevent disengagement and foster a sustainable work culture.